Larval morphology of Liodessus Guignot, 1939: Generic characteristics, descriptions of five species and comparisons with other members of the tribe Bidessini (Coleoptera: Dytiscidae: Hydroporinae) - Alarie, Yves (2007)
The larvae of Liodessus affinis (Say, 1823), L. crotchi Nilsson, 2001, L. flavofasciatus (Steinheil, 1869), L. involucer (Brinck, 1948), and L. patagonicus (Zimmermann, 1923) are described with an emphasis on chaetotaxy of the head capsule, head appendages, legs, last abdominal segment and urogomphi. Larvae of these species are very uniform in terms of larval morphology. Considering all known bidessine larvae, Liodessus Guignot, 1939 is more similar to Hypodessus Guignot 1939, Amarodytes Régimbart, 1900, Anodocheilus Babington, 1841, Glareadessus Wewalka & Biström, 1998, Allodessus Guignot, 1953, and Neoclypeodytes Young, 1967, all these genera sharing a short siphon and an elongate first urogomphomere. Liodessus differs from Hypodessus, Amarodytes and Anodocheilus by absence of the primary pore PAj whereas it shares with Anodocheilus the absence of a ventroapical spinula on the third antennomere.